INFLUENCE OF QUALITY INDICATORS OF WINTER WHEAT GRAIN ON BAKING PROPERTIES OF FLOUR - Картошка, Ольга; Олефир, Олег; Татарко, Юлия (SWorldJournal, 2021)
The article substantiates the relevance of a comprehensive assessment of a number of indicators of grain and flour quality, in order to determine the nutritional value of bakery products made from them. The aim of the study is to determine the impact of